Types of Dental Stools Used in Dentistry: Emphasis on Occupational Health - Hallak, Júlia Carrer [UNESP]; Garcia, Patricia Petromilli Nordi Sasso [UNESP] (Sciencedomain International, 2023)
Aims: This study aimed to perform a literature review on the types of stools used in Dentistry with emphasis on maintaining occupational health. Study Design: Literature review. Place and Duration of Study: Department of Social Dentistry, São Paulo State University (UNESP), School of Dentistry of Araraquara, São Paulo, Brazil, between January 2023 to July 2023. Methodology: The literature used in this review was obtained from databases (Science Direct, National Library of Medicine [MEDLINE] e Scientific Electronic Library Online), and only articles published between 1980 and 2022 were considered. The main keywords were “Dental Stool”, "Ergonomic Stool”, “Occupational Health”, and “Saddle Seat.” Each abstract was read to determine whether the information in the article included information on the use of stools during dental procedures. Results: The most studied dental stools were the normal and adapted conventional stool and the normal and adapted saddle seat in the 13 articles that met the inclusion criteria. Conclusion: The use of a saddle seat can help maintain healthy working posture and prevent musculoskeletal disorders in dentistry.